Early and Mid-Term Disposition of [alpha]-PVP and its unknown Metabolites in Urine and Oral Fluid Through a Multi-Analytical Hyphenated Approach Following a Single Non-Controlled Administration to Healthy Volunteers - Di Trana, Annagiulia; La Maida, Nunzia; de la Rosa, Georgina; Di Giorgi, Alessandro; Graziano, Silvia; Aldhaehri, Khaled; Papaseit, Esther (The AAPS journal, 2025)
Nowadays, synthetic cathinones (SCs) is the second more representative subclass of New Psychoactive Substances, accounting for 104 analogues in the illegal market. Since its first report in 2011, [alpha]-pyrrolidinovalerophenone ([alpha]-PVP) gained popularity among drug users, provoking an increased number of intoxications. Nonetheless, pharmacokinetics data is still limited in the literature. An observational non-controlled naturalistic study on 8 healthy volunteers was conducted to assess the [alpha]-PVP and -OH-[alpha]-PVP concentrations in OF and urine, after snorting 10 mg or 20 mg of [alpha]-PVP. A multi-analytical approach based on GC-EI-MS/MS and LC-HESI-HRMS/MS was developed and fully validated for the analytes quantification, while four untargeted LC-HESI-HRMS/MS methods in full-MS and ddMS.sup.2 were set up for unknown metabolites characterization in urine samples assisted by a dedicated data mining software. In OF, [alpha]-PVP reached a mean C.sub.max of 762 ± 323 ng/mL at 1 h after 10 mg administration, while a C.sub.max of 2,900 ± 1,373 ng/mL at 47 min after 20 mg dose. In urine, a total [alpha]-PVP mean amount of 179.2 ± 94.9 µg was accumulated after 10 mg dose, (27.2 ± 9.8 µg between 0-2 h and 152.0 ± 98.2 µg between 2-5 h), while a total amount of 122.9 ± 44.0 µg, of (36.2 ± 16.5 and 86.7 ± 28.3 µg between 0-2 and 2-5 h, respectively) was detected after 20 mg dose. Among the 10 identified metabolites, -OH-[alpha]-PVP was a minor metabolite (total amount: 56.4 ± 27.1 and 69.1 ± 38.1 µg after 10 mg and 20 mg). The N-butanoic acid metabolite was the most abundant, detected also as glucuronide. In conclusion, [alpha]-PVP showed a later time peak than non-pyrrolidine SCs, with comparable C.sub.max. The pyrrolidine ring oxidative opening produced the most abundant urinary metabolite, independently from the dose.